Positionality statements in science [version 2; peer review: 2 approved] - Veli-Matti Karhulahti (Open Research Europe, 2024)
The goal of this essay is to clarify positionality as an epistemological scientific concept and address related misunderstandings to help researchers assess whether statements thereof contribute to their work. Positionality statements can be useful for various research designs across scientific fields, when they are used knowingly.